Factors Associated with Anemia in Adolescents and Its Prevention Strategies: Systematic Review - Melani, Margareta; Supriyatin, Dedeh; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (JURNAL INFO KESEHATAN, 2024)
Anemia is a global health issue affecting various age groups, including teenagers. This systematic review aims to identify the causes and treatments of anemia in adolescents. Using the Systematic Literature Review method, data were sourced from four databases: PubMed, Science Direct, Google Scholar, and SCOPUS. The literature search employed the keywords "Risk factor" AND "Anemia" AND "Adolescence," conducted comprehensively via the Publish or Perish (POP) search engine. Articles were selected based on inclusion criteria, covering publications from the last three years (2021-2023). Eligibility was assessed using the PICOS framework, and duplications were filtered using the Covidence application. Articles unrelated to the research problem were excluded after screening titles and abstracts. The VOSviewer application was utilized for thematic mapping. The study selection followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Based on 18 selected articles, data was obtained on factors influencing anemia among adolescents such as inadequacy of nutrient intake (N=5 studies) such as protein, iron, and Vitamin A Nutritional status (N=3 studies), dietary patterns (N=2 studies), menstruation (N=2 studies), and hemoglobinopathies (N=1 study) are translated into English. Indirect risk factors associated with anemia among adolescents are found to be: Adolescent females (N=10 studies), Knowledge (N=6 studies), low socioeconomic status (N=3 studies), Education (N=2 studies), Demographics (2 studies), Shared toilet usage (1 study). The study concludes that young women are more susceptible to anemia than young men, with nutritional intake, knowledge, nutritional status, and diet being the primary risk factors. Addressing direct and indirect causes is crucial for effectively managing adolescent anemia.